Nonimaging optics : solar and illumination system methods, design, and performance - Winston, Roland; Jiang, Lun; Oliker, Vladimir, 1945- (Boca Raton, FL : CRC Press/Taylor & Francis Group, 2020)
"This book provides a comprehensive look at the science, methods, designs, and limitations of nonimaging optics. It begins with an in-depth discussion on thermodynamically efficient optical designs and how they improve the performance and cost effectiveness of solar concentrating and illumination systems"--
"Successor to Nonimaging Optics (Academic Press, 2005), by R. Winston, J. C. Miñano, and P. Benitez, with contributed chapters by N. Shatz and J. Bortz"--Preface.
OCLC-licensed vendor bibliographic record.
Keywords: Solar collectors -- Mathematical models; Light -- Transmission -- Mathematical models; Optical engineering -- Mathematics; Geometrical optics; TECHNOLOGY / Electricity; TECHNOLOGY / Lasers